School trajectory and teenage pregnancy in three Brazilian state capitals - Almeida Maria da Conceição C.; Aquino Estela M. L.; Barros Antoniel Pinheiro de (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2006)
This paper describes the relationship between school trajectory and incidence of teenage pregnancy. A cross-sectional residence-based questionnaire was applied, interviewing 4,634 youth ages 18 to 24 years, selected through a stratified three-stage sample. For the present study, young people ages 20 to 24 years (65.6%) were chosen, with teenage pregnancy rates of 29.5% for females and 21.4% for males (in relation to their partners). Sexual debut was reported by 87% of women and 95.3% of men. The majority of young people reported irregular school trajectory, with 39% enrolled in school at the time of the study. Nearly half of those who had interrupted their studies at least once reported a teenage pregnancy. The main reasons for interrupting their studies were pregnancy and children for women and work for men. School dropout due to teenage pregnancy was mentioned by 40.1% of women for whom the outcome of pregnancy was a child. However, 20.5% had already dropped out of school before becoming pregnant.